2017
DOI: 10.1159/000480153
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Monitored Anesthesia Care Using Propofol-Based Sedation for Pleuroscopy

Abstract: Background: The optimal approach to sedation for pleuroscopy remains undefined. Propofol is the favored sedative-hypnotic for many proceduralists but has a narrow therapeutic window and the risk for oversedation is high. Propofol-based sedation administered by anesthesiologists and the routine use of end-tidal capnography and bispectral index (BIS) monitoring may attenuate risks of complications. Objectives: The purpose of our study was to evaluate the safety and efficacy of monitored anesthesia care for pleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, end tidal CO 2 measurements were considered unreliable in a prior study where most patients showed false low-end tidal CO 2 levels due to an unsealed dual nasal cannula and room-air dilution of expired gases ( Ibrahim et al, 2019 ). Despite the fact that recent evidence supports the use of capnography in deep sedation, its use in moderate sedation has not been shown to improve patient safety ( Vakil et al, 2018 ). Despite various monitoring methods, the incidence of oxygen desaturation in this study was still relatively high, which may be due to inhibition of the respiratory centre in the brainstem by RF, especially when associated with benzodiazepines; hypoventilation secondary to sedation; and airway obstruction by the bronchoscope itself ( Zha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, end tidal CO 2 measurements were considered unreliable in a prior study where most patients showed false low-end tidal CO 2 levels due to an unsealed dual nasal cannula and room-air dilution of expired gases ( Ibrahim et al, 2019 ). Despite the fact that recent evidence supports the use of capnography in deep sedation, its use in moderate sedation has not been shown to improve patient safety ( Vakil et al, 2018 ). Despite various monitoring methods, the incidence of oxygen desaturation in this study was still relatively high, which may be due to inhibition of the respiratory centre in the brainstem by RF, especially when associated with benzodiazepines; hypoventilation secondary to sedation; and airway obstruction by the bronchoscope itself ( Zha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pleuroscopy was performed as per institutional standard of care, as previously described [10][11][12] (see Appendix S1 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxemic events (SpO 2 <90% for at least 2 min) were observed in 4 patients (7.6%), but all of them were resolved with gentle patient stimulation, while hypotensive events occurred in 34 (64.1%) patients, but vasopressors were needed in only 4 patients. Vakil and colleagues [26], in a retrospective cohort study of 199 patients, contended that propofol sedation with etCO 2 monitoring is a safe technique, though in this series the sedation was again performed by anesthesiologists. Specifically, no major complications were observed, and hypoxia (SpO 2 <90% for 2 min) and hypotension (need for vasopressors) occurred in 4.5% and 38.2%, respectively.…”
Section: Propofolmentioning
confidence: 99%